2006
DOI: 10.3732/ajb.93.10.1426
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mechanical properties of four large, wave‐exposed seaweeds

Abstract: Seaweeds have a simple structural design compared to most terrestrial plants. Nonetheless, some species have adapted to the severe mechanical conditions of the surf zone. The material properties of either tissue sections or the whole stipe of four wave-exposed seaweeds, Durvillaea antarctica, D. willana, Laminaria digitata, and L. hyperborea, were tested in tension, bending, and torsion. Durvillaea has a very low modulus of elasticity in tension (E(tension) = 3-7 MN·m(-2)) and in bending (E(bending) = 9-12 MN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 42 publications
5
79
4
Order By: Relevance
“…Conversely, Dudgeon and Johnson observed greater reconfiguration in a stiff species (Mastocarpus) than in a more flexible species (Chondrus) (Dudgeon and Johnson, 1992). Harder et al observed a correlation between tissue stiffness and exposure (Harder et al, 2006), suggesting that lower stiffness bestows greater reconfiguration and survival.…”
Section: Do Structural Properties Influence Hydrodynamicmentioning
confidence: 95%
See 2 more Smart Citations
“…Conversely, Dudgeon and Johnson observed greater reconfiguration in a stiff species (Mastocarpus) than in a more flexible species (Chondrus) (Dudgeon and Johnson, 1992). Harder et al observed a correlation between tissue stiffness and exposure (Harder et al, 2006), suggesting that lower stiffness bestows greater reconfiguration and survival.…”
Section: Do Structural Properties Influence Hydrodynamicmentioning
confidence: 95%
“…However, the torsion of branches may be important for the compaction of blades. Thus, variation in torsion modulus among macroalgal species (Harder et al, 2006) may influence reconfiguration. Further, tissue stiffness in compression and tension may differ and influence bending of branches (Koehl and Wainwright, 1977;Gaylord and Denny, 1997).…”
Section: Do Structural Properties Influence Hydrodynamicmentioning
confidence: 99%
See 1 more Smart Citation
“…Delf, 1932;Koehl, 1986;Carrington, 1990;Dudgeon and Johnson, 1992;Friedland and Denny, 1995;Blanchette, 1997;Gaylord, 1997;Bell, 1999;Denny and Gaylord, 2002;Boller and Carrington, 2006;Harder et al, 2006). One unifying characteristic that has been thoroughly explored in these studies is flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…the energy absorbed before breaking) was calculated from the area under a stress-strain curve, with an alga achieving toughness by being very strong, very extensible, or both. This property has been widely reported for marine plant tissues (Koehl and Wainwright, 1977;Armstrong, 1988;Patterson et al, 2001;Harder et al, 2006); however, the biological significance is unclear (Denny and Gaylord, 2002;Denny and Hale, 2003). Finally, we explored whether any apparent differences in those properties among the three subfamilies could be attributed to differences in cellular structure or cell wall thickness.…”
Section: Introductionmentioning
confidence: 99%